FAMILY EMPIDIDAE - Rafael, José Albertino; Câmara, Josenir Teixeira (Zootaxa, 2016)
Empididae is one of the biggest families of Diptera with around 3,000 known species. The family is poorly known in Colombia, with only six species reported and this work provides information on their distribution. No endemic genera or species have been recorded to date from Colombia.